A novel bioprocess combining anaerobic co-digestion followed by ultra-filtration and microalgae culture for optimal olive mill wastewater treatment. (1st February 2022) - Karray, Raida; Elloumi, Wièm; Ben Ali, Rihab; Loukil, Slim; Chamkha, Mohamed; Karray, Fatma; Sayadi, Sami
Abstract: Treatment of olive mill wastewater (OMW) has received considerable research globally due to its influence on the technical, economic, and environmental sustainability of wastewater biogas production. This work presents a novel combined biological process for OMW treatment in terms to produce for the first time, treated OMW and a valuable microalgae biomass. The process involves anaerobic co-digestion (AD), a low cut-off membrane ultra-filtration (UF) and a subsequent Scenedesmus sp. culture. The AD of OMW was conducted at high initial COD ranging from 28 to 38 g/L using an up-flow anaerobic fixed bed bio-reactor (300 L). Results revealed that the maximum biogas production was about 0.507 L/g CODintroduced .day containing 73% of methane corresponding to a methane yield of 0.370 L/g CODintroduced .day obtained at an organic loading rate of 4.58 g COD/L.day. High removal levels of COD, total phenolic compounds, and total suspended solids in the anaerobic liquid digestate (ALD) were achieved after AD and UF. Scenedesmus sp. was then cultivated on the ultra-filtrated ALD. A maximum biomass productivity of 0.15 g/L.day was recorded when Scenedesmus sp. is grown on 25% of ultra-filtrated ALD with a maximum nitrogen removal rate of 15.18 mg/L.day and an almost total elimination of phosphorus and phenolic compounds. Highlights: Olive mill wastewater (OMW) was used as feedstock for methane-rich biogas production. The digestate was used as feedstock for Scenedesmus sp. cultures. UF-ALD of OMW enhances the Scenedesmus sp. biomass productivity to 0.15 g/L.day. The novel combined bioprocess produces biogas, treated OMW and a valuable algae biomass.